2014
DOI: 10.4103/0973-1482.136549
|View full text |Cite
|
Sign up to set email alerts
|

Prognostics of Cyclin-D1 expression with chemoradiation response in patients of locally advanced oral squamous cell carcinoma

Abstract: The high Cyclin-D1 expression may serve as a poor prognostic marker in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A key focus for researchers has been the role of cyclin D1 in loco-regional lymph node metastasis. Many authors found a significant correlation between cyclin D1 overexpression or gene amplification and N stage (Mineta et al, 2000;Carlos de Vicente et al, 2002;Myo et al, 2005;Wang et al, 2006b;Das et al, 2011;Mahdey et al, 2011;Huang et al, 2012;Gupta et al, 2014;van Kempen et al, 2015), and this association has been corroborated by two meta-analyses (Zhao et al, 2014;Noorlag et al, 2015). Extracapsular spread, one of the worst prognostic features in oral cancer, has been positively correlated with CCND1 copy-number aberrations in primary tumors (P = 0.011; Michikawa et al, 2011).…”
Section: Tumor Size and Clinical Stagementioning
confidence: 90%
See 4 more Smart Citations
“…A key focus for researchers has been the role of cyclin D1 in loco-regional lymph node metastasis. Many authors found a significant correlation between cyclin D1 overexpression or gene amplification and N stage (Mineta et al, 2000;Carlos de Vicente et al, 2002;Myo et al, 2005;Wang et al, 2006b;Das et al, 2011;Mahdey et al, 2011;Huang et al, 2012;Gupta et al, 2014;van Kempen et al, 2015), and this association has been corroborated by two meta-analyses (Zhao et al, 2014;Noorlag et al, 2015). Extracapsular spread, one of the worst prognostic features in oral cancer, has been positively correlated with CCND1 copy-number aberrations in primary tumors (P = 0.011; Michikawa et al, 2011).…”
Section: Tumor Size and Clinical Stagementioning
confidence: 90%
“…Higher levels of cyclin D1 expression have been found in OSCCs of larger size (Carlos de Vicente et al , ; Das et al , ; Gupta et al , ; Guimarães et al , ). In their meta‐analysis, Zhao et al (Zhao et al , ) reported a significant correlation between cyclin D1 overexpression and higher T stage.…”
Section: Diagnostic and Prognostic Implications Of Cyclin D1 In Oral mentioning
confidence: 99%
See 3 more Smart Citations